Kinnier Wilson's puzzling features of amyotrophic lateral sclerosis - Turner, MR; Eisen, A; Kiernan, MC; Ravits, J; Swash, M (BMJ Publishing Group, 2017)
Pre-eminent neurologist S.A. Kinnier Wilson’s posthumously published 1940 textbook ‘Neurology’ included a detailed clinicopathological account of the neurodegenerative disorder amyotrophic lateral sclerosis (ALS). In providing a comprehensive discussion of the breadth of the clinical heterogeneity, he highlighted five “puzzling features” that appear prescient of the modern recognition of ALS as a complex multisystem syndrome. The issues he raises span the areas of ongoing debate and active research in ALS, including clinical and pathological discordance, upper versus lower motor neuron loss, and the apparent non-random onset and spread of clinical symptoms. We discuss each of his observations in light of the great advances in histopathology, molecular biology, neurophysiology and neuroimaging over the subsequent 75 years.